A capsular polysaccharide from a healthy human microbiota member activates a Lag-3-NK cell axis to restrain colon cancer and augment immunotherapy - Allison M. Weis; Kaylyn M. Bauer; William W. Tang; Emmanuel Stephen-Victor; Rickesha Bell; D. Garrett Brown; H. Atakan Ekiz; Van Tran; Kendra A. Klag; Eric A. Swanson; Logan Barrios; Morgan Harwood; et al. (Cell Reports)
Summary: Colorectal cancer (CRC) is increasing globally, making identification of preventative measures necessary. Transplantation of the microbiota from CRC and non-CRC patients into mice demonstrates that non-diseased individuals possess organisms that reduce tumor formation and highlights Bacteriodes uniformis as protective. B. uniformis is reduced in humans with CRC, and proactive treatment with B. uniformis slows tumor growth in mice. Natural killer (NK) cells, but not T cells, are required for B. uniformis-mediated protection. CRC is recalcitrant to immunotherapies; however, addition of B. uniformis restores response to α-CTLA-4 treatment in an NK cell-dependent manner. We report that high Lag-3 expression is associated with greater survival in CRC patients and that B. uniformis-mediated protection is reliant on Lag-3 in innate cells. Induction of NK cell activity and reduced tumor growth is dependent on a specific B. uniformis capsular polysaccharide. Thus, healthy individuals possess tumor suppressor microbes that prevent cancer development and can be harnessed therapeutically.